2019
DOI: 10.1002/jbm.a.36658
|View full text |Cite
|
Sign up to set email alerts
|

Use of affinity allows anti‐inflammatory and anti‐microbial dual release that matches suture wound resolution

Abstract: Surgical sutures are vulnerable to bacterial infections and biofilm formation. At the suture site, pain and undesirable, excess inflammation are additionally detrimental to wound healing. The development of a polymerized cyclodextrin (pCD) coated surgical suture introduces the capability to locally deliver both anti‐inflammatory and anti‐microbial drugs throughout the phases of acute and chronic healing. Local delivery allows for the improvement of wound healing while reducing related systemic side effects and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Resveratrol was dissolved in DMF at 5 wt % and pCD disks were exposed to this loading solution for 3 days at room temperature to allow for drug loading. Optimization of resveratrol concentrations for drug loading into pCD indicated that an increase in resveratrol concentration during drug loading can increase the weight percent loading achieved in pCD polymer disks, therefore determining the loading concentration utilized in the study herein [90]. Loaded pCD was then removed from the solution, blotted, and briefly washed in excess water to remove surface DMF and free (uncomplexed) resveratrol prior to drying at room temperature.…”
Section: Resveratrol Loading Into Pcdmentioning
confidence: 99%
“…Resveratrol was dissolved in DMF at 5 wt % and pCD disks were exposed to this loading solution for 3 days at room temperature to allow for drug loading. Optimization of resveratrol concentrations for drug loading into pCD indicated that an increase in resveratrol concentration during drug loading can increase the weight percent loading achieved in pCD polymer disks, therefore determining the loading concentration utilized in the study herein [90]. Loaded pCD was then removed from the solution, blotted, and briefly washed in excess water to remove surface DMF and free (uncomplexed) resveratrol prior to drying at room temperature.…”
Section: Resveratrol Loading Into Pcdmentioning
confidence: 99%
“…LND also has poor solubility, increasing the difficulty of successfully delivering it to the area of treatment. In previous work, we have leveraged polymerized CDs (pCD) to continuously deliver hydrophobic, small molecule drugs on the order of weeks to months by leveraging affinity interactions [10][11][12][13][14][15][16][17][18][19][20][21] . A high concentration of affinity complexation sites to delay drug release is achieved by polymerizing CD monomers into larger disk structures, coatings, and more [11][12][13][22][23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…Most research on the delivery of bioactive molecules via surgical sutures has been focused on coating techniques. 262,263 In previous studies, suture surfaces bound with MMP inhibitor and coated with ECM compounds (e.g., collagen and laminin), resulted in the successful restoration of ECM organization. 264 However, one of the major drawbacks of the coating strategy is that the bioactive molecules are almost fully exposed to the surrounding tissues, which causes a rapid bolus release in the initial stage.…”
Section: Wearable Wound Monitorsmentioning
confidence: 99%